2009
DOI: 10.1007/s00280-009-1200-9
|View full text |Cite
|
Sign up to set email alerts
|

Novel microtubule-targeting agents, pyrrolo-1,5-benzoxazepines, induce apoptosis in multi-drug-resistant cancer cells

Abstract: Our results suggest that pro-apoptotic PBOX compounds may be potential candidates for the treatment of P-glycoprotein- or BCRP-associated MDR cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 32 publications
(47 reference statements)
4
26
0
Order By: Relevance
“…These values are within a similar range (1-6 and 0.2-0.4 μM for PBOX-6 and -15, respectively) to those observed in other cell lines such as CML K562 cells, promyelocytic leukaemia HL60 cells, ovarian carcinoma A2780 cells and a range of mammary carcinoma cell lines (10,11,14,16). This reduction in PC3 cell proliferation was mediated through a significant G 2 /M arrest followed by treatment for 24 h in either fresh media (as a control) or media containing flavopiridol (0.1-0.5 μM).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…These values are within a similar range (1-6 and 0.2-0.4 μM for PBOX-6 and -15, respectively) to those observed in other cell lines such as CML K562 cells, promyelocytic leukaemia HL60 cells, ovarian carcinoma A2780 cells and a range of mammary carcinoma cell lines (10,11,14,16). This reduction in PC3 cell proliferation was mediated through a significant G 2 /M arrest followed by treatment for 24 h in either fresh media (as a control) or media containing flavopiridol (0.1-0.5 μM).…”
Section: Discussionsupporting
confidence: 62%
“…Much of this resistance is thought to be mediated through expression of the multidrug-resistance transporter, P-glycoprotein or by microtubule alterations (21). In addition to inducing apoptosis in a variety of cancerous cell types (5-9) and impairing tumour growth in vivo (11,12), novel pyrrolo-1,5-benzoxazepine (PBOX) compounds possess the added benefit of inducing cytotoxicity in multidrug-resistant cancer cells expressing P-glycoprotein with similar potency as in P-glycoprotein-negative cancer cells (14). Furthermore, they appear to induce tubulin depolymerisation by binding to a novel as yet uncharacterized site on tubulin (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition we have also found that PBOXs displayed anti-angiogenic properties in vitro (10). An added advantage of PBOX compounds over many clinically used 4 anti-cancer agents such as docetaxel is that they do not appear to be substrates of the ABCtransporters, P-glycoprotein and BCRP, since they are capable of inducing apoptosis in multidrug-resistant cancer cells expressing these transporters with similar efficacy as in transporter-negative drug-sensitive cells (14). The PBOX compounds exert their effects by binding to an uncharacterised site on tubulin resulting in microtubule depolymerisation (15).…”
Section: Introductionmentioning
confidence: 61%
“…16 In particular, PBOX-15 is a tubulin depolymerizing agent displaying a proapoptotic activity in a variety of human solid and hematological malignancies, [16][17][18][19][20][21] with minimal toxicity toward normal blood and bone marrow cells. 17 In the present study we identified PBOX-15 as a submicromolar selective inhibitor of FAAH enzyme (IC50= 0.843 mM) and we investigated the anti-tumor efficacy and mode of action of this compound on CRC cell lines.…”
Section: Introductionmentioning
confidence: 99%